Investigation of heat transfer phenomena and flow behavior around electronic chip - Habeeb, Sattar j. (Al-Khwarizmi Engineering Journal, 2007)
Computational study of three-dimensional laminar and turbulent flows around electronic chip (heat source) located on a printed circuit board are presented. Computational field involves the solution of elliptic partial differential equations for conservation of mass, momentum, energy, turbulent energy, and its dissipation rate in finite volume form. The k-ε turbulent model was used with the wall function concept near the walls to treat of turbulence effects. The SIMPLE algorithm was selected in this work. The chip is cooled by an external flow of air. The goals of this investigation are to investigate the heat transfer phenomena of electronic chip located in enclosure and how we arrive to optimum level for cooling of this chip. These parameters, which will help enhance thermal performance of electronic chip and flow patterns, through the understanding of different factors on flow patterns. The results show the relation between the temperature rise, heat transfer parameters (Nu, Ra) with (Ar, Q) for two cases of laminar and turbulent flows.